Women’s Use Of Indigenous Knowledge Systems To Cope With Climate Change - Sithole, Angeline; Lekorwe, Mogopodi (Advances in Social Sciences Research Journal, 2019)
This research seeks to ascertain the indigenous knowledge systems that are employed to address the impact of climate change, to examine the effectiveness of these coping strategies, and to suggest possible ways of ensuring sustainability of the strategies employed. There are global climate change policies and mechanisms which serve to guide on ways in which climate change should be considered, they include the United Nations Framework Convention on Climate Change, the Kyoto Protocol, the IPCC 2007 Fourth Assessment Report on Climate Change Impacts, Adaptations and Vulnerability and the Stern Review on the economies of climate change -2006. Indigenous knowledge systems (IKS) are highlighted with the history of these IKS being outlined thereafter the different uses of IKS in various countries are addressed. This desk top research therefore reveals reasons why women should be entrusted with the IKS. The major issue being that women are the ones who labour in the fields and constitute 80% of the agricultural work force and contribute 50%-80% of the work in the fields. They are the ones who are suitably equipped with the various strategies of coping with climate change and predicting the weather so as to ensure food security for their families. Women, however, face challenges in the use of the IKS, chief amongst these challenges is the patriarchal tradition which does not allow them to contribute in decision making.